PERTUMBUHAN DAN PRODUKSI TANAMAN JEWAWUT [SETARIA ITALICA (L.) P. BEAUV.] PADA PERLAKUAN DOSIS RADIASI DENGAN PENGURANGAN FREKUENSI PENYIRAMAN UNTUK SELEKSI TOLERAN KEKERINGAN - Hidayati, Nuril; Syarif, Fauzia (Perhimpunan Biologi Indonesia, 2019)
ABSTRACTFoxtail millet [Setaria italica (L.) Beauv.] is one of potential cereal plants that can be developed as a source of carbohydrates in marginal and dry lands. The purpose of this study was to examine the tolerance to drought of foxtail millet accession of Buru Merah as a result of gamma radiation treatment. In this study, the seeds of the Buru Merah accession were treated with gamma ray at doses of 0, 25, 50, 100 and 200 Gy. The established growing plants were then treated with different intervals of watering, which were every day (as control), 2 days, 4 days, and 6 days which were arranged in factorial randomized block design with three replications. The observed variables were increase plant height, increase of leaf number, leaf chlorophyll content, plant water potential and yields. The results revealed that the radiation treatment did not show any significant difference in the production of plant biomass. With radiation treatments of 0, 25, 50 and 100 Gy. and a two-day watering interval the plants can still maintain its water potential above -3 MPa and showing optimum growth. However radiation treatment resulted a significant difference in panicle production, especially between the radiation dose of 200 Gy. and others. The combination of 0-100 Gy. radiation treatment and 2-day watering interval produced plants with optimum panicle production.Keywords: drought, growth, millet, production, radiation, tolerant